Scar endometriosis following caesarean section: a rare case report - Sharma, Manisha; Nautiyal, Ruchira; Chaturvedi, Jaya; Bhargava, Surbhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Endometriosis is presence of functioning endometrial tissue (glands and stroma) outside the uterine cavity. Endometriosis can sometimes occur in previous surgical scar. Scar endometriosis is rare and difficult to diagnose. It mostly follows obstetrical and gynaecological surgeries. We present here a case report of a patient who developed scar endometriosis following a caesarean section which was dealt adequately in the subsequent caesarean section.